Spiritual Quontient: Pengaruhnya terhadap Etika Berkomunikasi Mahasiswa - Nalia, Sonia Tri; Pratama, Farhan Fajar; Sasferi, Nuzmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to analyze the influence of Spiritual Quotient (SQ) on the communication ethics of university students. The research sample consisted of 128 students. The research instruments used were SQ and communication ethics questionnaires. Data analysis was performed using descriptive statistics and simple regression. The results showed that: (1) the SQ of the students was in the high category (41%) and (2) the communication ethics of the students was in the high category (32%). The results of the simple regression analysis showed that there was a significant relationship between SQ and communication ethics of students with a significance value of 0.000. The coefficient of determination (R Square) of 0.241 indicates that 24.1% of the variation in students' communication ethics is explained by SQ.